2021
DOI: 10.1111/jcmm.16855
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin improves memory deficits by inhibiting HMGB1‐RAGE/TLR4‐NF‐κB signalling pathway in APPswe/PS1dE9 transgenic mice hippocampus

Abstract: Amyloid‐β (Aβ) deposition in the brain has been implicated in the development of Alzheimer's disease (AD), and neuroinflammation generates AD progression. Therapeutic effects of anti‐inflammatory approaches in AD are still under investigation. Curcumin, a potent anti‐inflammatory and antioxidant, has demonstrated therapeutic potential in AD models. However, curcumin's anti‐inflammatory molecular mechanisms and its associated cognitive impairment mechanisms in AD remain unclear. The high‐mobility group box‐1 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…In the obstructive nephropathy model, curcumin (50 mg/kg) by gavage inhibited the renal in ammatory response via suppressing TLR4/NF-κB signaling pathway [38] . Oral administration of curcumin (100 mg/kg) effectively reduced the expression of HMGB1 and the protein levels of TLR4 and NF-κB in the hippocampus of transgenic mice, thereby improving the memory de cit of transgenic mice [39] . Intraperitoneal injection of 100 mg/kg curcumin in rats down-regulated the expression of TLR4 and NF-κB, and inhibited the production of in ammatory cells, thereby improving hindlimb motor defects and spinal cord edema caused by spinal cord injury in rats [40] .…”
Section: Discussionmentioning
confidence: 99%
“…In the obstructive nephropathy model, curcumin (50 mg/kg) by gavage inhibited the renal in ammatory response via suppressing TLR4/NF-κB signaling pathway [38] . Oral administration of curcumin (100 mg/kg) effectively reduced the expression of HMGB1 and the protein levels of TLR4 and NF-κB in the hippocampus of transgenic mice, thereby improving the memory de cit of transgenic mice [39] . Intraperitoneal injection of 100 mg/kg curcumin in rats down-regulated the expression of TLR4 and NF-κB, and inhibited the production of in ammatory cells, thereby improving hindlimb motor defects and spinal cord edema caused by spinal cord injury in rats [40] .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, there was an increase in GFAP (a marker of astrocytes) expression in the dentate gyrus region of the hippocampus following LPS-induced neuroinflammation, though no significant increase in GFAP immunoreactivity was observed; curcumin was found to significant decrease GFAP immunoexpression. Chronic curcumin exposure has been documented to increase synaptophysin and actin expression and reduce GFAP expression in the hippocampus [36,37], while simultaneously reducing the reactive oxygen species (ROS) -related molecule, metallothionein 3 expression in the prefrontal cortex (PFC) and hippocampus [36]. This curcumin administration has been proposed to be a promising agent to attenuate memory deterioration in mice by inhibiting the HMGB1-RAGE/TLR4-NF-κB inflammatory signaling pathway [37].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Han et al [ 43 ] also reported the potential of curcumin ( Figure 3 ) to treat the cognitive impairment in a transgenic mice model claiming the possibility of inhibiting the HMGB1/RAGE inflammatory pathway [ 43 ]. For the evaluation of curcumin, they used APP/PS1 transgenic mice for the diseased group, and wild type (WT) mice as the control.…”
Section: Molecules Targeting Hmgb1/rage Axis In Various Inflammatory ...mentioning
confidence: 99%
“…The expression of all these proteins was significantly increased in the hippocampus of the diseased mice (APP/PS1 mice) compared to WT. It is noteworthy that curcumin did not affect the plaque load in the hippocampus of the transgenic mice suggesting the possible mechanism of curcumin to show neuroprotection specifically through the HMGB1/RAGE inflammatory pathway [ 43 ].…”
Section: Molecules Targeting Hmgb1/rage Axis In Various Inflammatory ...mentioning
confidence: 99%